Gurupá - das ruínas aos cemitérios Gurupá: from the ruins to the cemeteries - Gunter Karl Pressler (Estudos Avançados, 2012)
Posterior ao Tratado de Madrid (1750), o governo do Marquês de Pombal (1750-1777) implanta o projeto moderno nacional de caráter imperial nas colônias portuguesas. O Tratado de Madrid reconhecia a situação real na América Latina e encaminhou o trabalho das comissões de limites. O capitão-geral, na época do Estado do Grão-Pará e Maranhão, Francisco Xavier Mendonça Furtado foi ator decisivo do projeto político e militar, segurando a região à coroa portuguesa, e executava o projeto pombalino contra os jesuítas ("Estado de Deus") e as condições agrestes da região. A partir dos traços que o empreendimento político e ideológico deixou, o nosso estudo compara três vozes: as cartas do Governador Francisco Xavier de Mendonça Furtado, a obra do escritor paraense Dalcídio Jurandir e a trilogia romanesca de Alfred Döblin, a fim de analisar como as incursões ideológica e estética configuram a mediação entre a realidade histórica e a representação nas narrativas de ficção. Essa comparação se realiza no contexto de uma região que liberou as mais altas e fecundas fantasias da historia cultural da humanidade (as Amazonas, El Dorado, o tesouro do Rei Salomão e o boom da borracha), a fim de traçar as fantasmagorias diante das ruínas da realidade, confrontar o imaginário coletivo e a ficcionalização individual. Prime Minister Marques de Pombal (1750-1770) begins his mandate after the Treaty of Madrid (1750) a modern political enterprise of "nationalization" of the colonies. The Treaty has recognized the de facto occupation, and transferred sovereignty of about half of the Amazon basin from Spain to Portugal. The political project has been executed by Francisco X. Mendonça Furtado against the Jesuits "State of God" who 'protected Indians from slavery and settlers in vast semi-autonomous tracts of territory . By drawing our attention to political and ideological appropriations(the concept of the modern individual/state), and the traces left by social memory (personal e officinal letters) and fictional literature (romances), such flows of people, ideas, images and ideals challenge us to rethink the character of phantasmagoria and fictional values of belonging, formation and identity. This study compare three voices: the letters of the Portuguese ambassador-traveler Francisco X. Mendonça Furtado, the Amazon Trilogy of Alfred Döblin and the work of the native novelists Dalcídio Jurandir to knowing how political and aesthetic imagination inflected or configured the individual creative enquire and in which form are collectively of Amazonia (Nationalization and Culture) imagined or represented. This comparative study especially considering the regional background which liberate one of the most potentialities of imagination and confronting in dialogic interaction the Phantasmagoria with the ruins of the reality, the political imagination with the narrative fictionalisation..